Mechanisms of SecM-Mediated Stalling in the Ribosome - Gumbart, James (The Biophysical Society, 2012)
Nascent-peptide modulation of translation is a common regulatory mechanism of gene expression. In this mechanism, while the nascent peptide is still in the exit tunnel of the ribosome, it induces translational pausing, thereby controlling the expression of downstream genes. One example is SecM, which inhibits peptide-bond formation in the ribosome's peptidyl transferase center (PTC) during its own translation, upregulating the expression of the protein translocase SecA. Although biochemical experiments and cryo-electron microscopy data have led to the identification of some residues involved in SecM recognition, the full pathway of interacting residues that connect SecM to the PTC through the ribosome has not yet been conclusively established. Here, using the cryo-electron microscopy data, we derived the first (to our knowledge) atomic model of the SecM-stalled ribosome via molecular-dynamics flexible fitting, complete with P- and A-site tRNAs. Subsequently, we carried out simulations of native and mutated SecM-stalled ribosomes to investigate possible interaction pathways between a critical SecM residue, R163, and the PTC. In particular, the simulations reveal the role of SecM in altering the position of the tRNAs in the ribosome, and thus demonstrate how the presence of SecM in the exit tunnel induces stalling. Finally, steered molecular-dynamics simulations in which SecM was pulled toward the tunnel exit suggest how SecA interacting with SecM from outside the ribosome relieves stalling.